The Children's Friend Society in the Cape of Good Hope and the question of labour c. 1830-1842 - Williams, Kate (Department of Historical Studies, 2022)
This dissertation follows the lives of the children under the care Captain Brenton's Children's Friend Society to the Cape Colony in the period 1833- 1842. Using the works of prominent Cape Colony historians such as Banks, Worden and Ross, l give an overview of the Cape Colony around the time of emancipation. My work includes an in depth study of the results of the 1839 Commission of Inquiry, which contained summaries of over 400 interviews with CFS apprentices stationed in the Cape Colony. Furthermore, I place great emphasis on the reporting by The Times in London on the activities of the CFS. My research highlights their humanitarian and anti-slavery rhetoric with regards to the children. This work attempts to highlight the role of the Times in the falling of the Society, the treatment of the children in the Cape and the failure of the parties involved to enact any change in the situations experienced by the CFS apprentices.